Efficient H2 production by photocatalytic water splitting under UV or solar light over variously modified TiO2-based catalysts. (7th June 2019) - Fiorenza, R.; Sciré, S.; D'Urso, L.; Compagnini, G.; Bellardita, M.; Palmisano, L.
Abstract: This paper focused for the first time on the comparison between three different approach to modify the chemico-physical properties of TiO2 -based photocatalysts and their effect in the H2 production by photocatalytic water splitting both under UV and solar light irradiation, under the same experimental conditions. The application of pulsed laser irradiation to aqueous TiO2 suspensions (first approach) induced structural transformations both on the bulk and on the surface of TiO2, boosting the H2 production, under UV light irradiation, of almost three times (20.9 mmol/gcat ·h) compared to bare TiO2 (7.7 mmol/gcat ·h). The second strategy was based on a templating method to obtain TiO2 with a macroporous structure to favour an efficient light absorption process inside the material pores, thus allowing a high H2 production (0.64 mmol/gcat ·h) under solar light irradiation. This performance was further enhanced when the macroporous TiO2 was coupled with CeO2 or W (third approach). In the latter case the H2 production increased to 0.72 mmol/gcat ·h for macroporous TiO2 CeO2 and to 0.82 mmol/gcat ·h for macroporous TiO2 W. This work highlights how it is possible to tune the TiO2 photocatalytic properties with easy and green procedures to obtain environmental friendly catalyst for hydrogen production. Graphical abstract: Image 1 Highlights: Different strategies were applied to improve the water splitting photocatalytic performance of anatase TiO2 . Pulsed laser treatments strongly enhanced the photoactivity mainly under UV light. The use of macroporous TiO2 boosted the photoactivity mainly under visible light. The activity of macroporous TiO2 was further increased by the presence of CeO2 or W.